Las Bambas: Social conflict 2015 - Pinto Herrera, Honorio (2018)
The study deals with the mining project Las Bambas (Apurímac) and the social conflict that broke out at the end of September 2015. The social protest was brief but intense; So much so that the government had to declare a state of emergency and take a series of measures to avoid escalating the conflict because in those days «Lima was the economic capital of the world.» The paper tries to demonstrate that the protests had objective motivations because the changes made by the Chinese company (MMG) were substantial, as they will damage areas of direct and indirect influence. The magnitude of the protest brought to the fore issues such as territorial planning, ecological economic zoning, prior consultation, public hearings, social license, extractivism, environmental pollution, etc. The conflict in the Las Bambas, with some peculiarities, is the portrait of others that have occurred in the great mining of Peru.